The Implementation of Herringbone Technique To Improve Student’s Reading Comprehension of The Eight Grade Student’s at UPT SMP Negeri 2 Pangsid - Agung Perdana; Patahuddin; Nasrullah (La Parole : Journal of Language Teaching and Pedagogy, 2019)
This research is based on students' problems related to learning English, especially in students' reading comprehension skills, where students have difficulty understanding the content of texts in English lessons, especially in terms of reading texts. In addition, this study applies the use of Herringbone Technique to assist students in improving their reading comprehension skills. Reading is defined as a scanning process that involves deciphering symbols, words to explain the meaning contained. Herringbone technique is a technique that can give students the opportunity to more easily find ideas contained in a reading with six comprehension questions (5W+1H). The researcher used a pre-experimental design, with two groups of test designs including pre-test and post-test. The research sample consisted of 21 students from one class taken from the eighth grade population at UPT SMP Negeri 2 Pangsid. This research consists of three stages including: preparation stage, implementation stage, and data analysis stage. The instrument used in this study is a reading comprehension test sheet which aims to determine the extent to which students' learning abilities are. The results of the tests carried out and data analysis found that students' reading comprehension abilities increased after treatment. With this, the average value of the pretest is 55.23 and the postest is 78.09. From these data, the reading comprehension ability of eighth graders at UPT SMP Negeri 2 Pangsid increased by using the Herrinbone technique. By analyzing the data manually, the result of the t-test score (11.442) is higher than the t-table (a 0.05, from df 21-1 = 20 students = 1.725 This means that the achievement of the eighth grade students' reading comprehension ability at UPT SMP Negeri 2 Pangsid has a significant increase. In conclusion, the use of the Herringbone technique can and is used to improve the understanding of eighth grade students at UPT SMP Negeri 2 Pangsid for the 2021/2022 academic year.